PENENTUAN METODE ANGSURAN MURABAHAH (Studi Kasus di BMT Al-Karomah Martapura) - Noval, MUHAMMAD (IAIN Antasari, 2015)
Abstract: This study aims to describe the practice of murabaha, and determination murabaha install-ment payment that used by BMT Al-Karomah Martapura. The object of this research is the determina-tion mechanism of murabaha installment payment method at BMT Al-Karomah in Martapura ob-tained through explanations of the managers of BMT Al-Karomah the Martapura. The method in thisresearch is a field research, which is the author explore the data directly from the field in accordancewith the problems studied. This research resulted several findings; First: Practice murabaha transactionsat BMT Al-Karomah Martapura is based on order and is consumptive and in the settlement of paymentby way of installments. Second: BMT Al-Karomah Martapura apply four methods for murabaha install-ment payments, namely: average profit margins, declining profit margins, flexible and voluntarily method.